Samband mellan hög incidens ämnesomsättningssjukdomar och klövhälsa hos svenska mjölkkobesättningar - Andersson, Magnus (2008)
Metabolic diseases in dairy cows are considered to increase the risk for claw lesions, most of all laminitis, sole haemorrhages and sole ulcers, but also to increase the risk for environmental claw lesions. The aim of this study was to compare claw health in 27 Swedish dairy farms, 18 with high incidence of metabolic diseases and 9 with low incidence. Data on claw health status was retrieved from recordings at routine claw trimmings and analysed on herd level regarding the prevalence of: any lesion, interdigital dermatitis, heel-horn erosion, sole haemorrhages, sole ulcer, lameness, abnormal claw shape, and other diseases (abscess in the white line, limb disorders, double sole, laminitic groove, white line disease, interdigital phlegmon, interdigital hyperplasia, toe abscess and verucose dermatitis). Mean prevalence of any lesion for herds with low incidence of metabolic diseases was 48 % and in herds with high incidence 41 %, and there was no statistical difference between the two groups. Mean prevalence for interdigital dermatitis was 2,0 % and 6.4 % in the low and high incidence groups, respectively (p<0.001). Mean prevalence for heel horn erosion was 12.7 % and 17.3 % in the low and high incidence groups, respectively (p<0.001). Sole ulcer was more prevalent in the low incidence group, with a mean prevalence of 6.1 % and 4.0 % for the low and high incidence groups, respectively (p<0.001). Sole haemorrhages was also more prevalent in the low incidence group, with a mean prevalence of 25 % and 19.3 % in the low and high incidence groups, respectively (p<0.001). There was no recorded lameness in the low incidence group, while the mean prevalence in the high incidence group was 0.9% (p<0.05). Abnormal claw shape was more prevalent in the high incidence group, with the mean prevalence in the low incidence group being 0.1 % and in the high incidence group 5,0 %, but there was no difference between the two groups regarding the other diseases. Stratifying the analysis of any lesion by stall type showed that there was no difference between the two groups when housed in tie stalls (20.4 % and 21.8 % in low and high groups respectively). However, the claw health was better in the high incidence group in free stalls with slatted concrete flooring (64.4 % and 43.5 % in low and high groups, respectively). In herds with solid concrete flooring the claw health was better in the low incidence group, with a mean prevalence of 25.8 % and 44.5 % in the low and high groups, respectively. Stratifying the analysis of any lesion by feeding regimen showed that there was no difference in claw health between the low and high incidence herds that were using total mixed rations (TMR) or between low and high herds using conventional concentrate and forage. However, herds using TMR had higher prevalence than the other herds. A number of different factors interact in causing claw health problems. Metabolic diseases and feeding is one part of the problem, but other factors like environment, flooring and how the heifers are introduced to the older cows play a part in the origin of claw lesions. Hoof trimmer's attitude and ability to record claw lesions differ and this may affect the result in studies like this using hoof health data recorded at routine claw trimming.